Pentalogy of Cantrell associated with unilateral anophthalmia: Case report and literature review. Issue 31 (August 2018) - Grigore, Mihaela; Furnica, Cristina; Esanu, Irina; Gafitanu, Dumitru
Abstract: Rationale: Pentalogy of Cantrell, a very rare congenital condition, has an estimated incidence of 5.5 per 1 million live births. It includes five defects: a midline supraumbilical wall defect, a diaphragmatic defect, a cleft distal sternum, a defect in the diaphragmatic pericardium, and an intracardiac defect. Very few cases of this condition have been reported in the literature, most of them diagnosed in the second or third trimester of pregnancy. Patient concerns: We present a case of pentalogy of Cantrell associated with cranioschisis and unilateral anophthalmia diagnosed at 14 weeks of amenorrhea. Diagnoses: The combination of abdominal and vaginal sonography established the diagnosis of 14 weeks of amenorrhea with a plurimalformative syndrome including: ectopia cordis, large suprambilical anterior abdominal wall defect, omphalocele, anomaly of the shape of the skull, and anomalies of the brain. Interventions: After counseling the parents, the pregnancy was interrupted, as requested by the family. Outcomes: Pathological examination of the fetus after the therapeutic abortion confirmed the diagnosis. Lessons: Because of the poor prognosis of Cantrell's pentalogy, early antenatal sonographic detection is important and allows for elective abortion before viability.